Produção científica na Faculdade de Filosofia, Ciencias e Letras de Ribeirao Preto-USP: Aplicação do índice de hirsch - Herculano, Rondinelli D.; Torro-Alves, Nelson; Terçariol, César S.A.; Norberto, Ana Maria Q.; Graeff, Carlos Frederico de Oliveira [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2008)
In this work, an analysis of scientific bibliographic productivity was made using the Faculdade de Filosofia, Ciencias e Letras de Ribeirao Preto, Universidade de Sao Paulo (FFCLRP-USP) as example. It is a special Institution in the Brazilian University system which encompasses four important areas of knowledge (fields of concentration) in natural, biological, humanities, and social areas. It is composed by four departments which offer altogether eight undergraduate courses: 1) Psychology, 2) Pedagogy, 3) Chemistry, 4) Biology, 5) Medical Physics, 6) Biomedical Informatics, 7) Sciences of Information and Documentation and 8) Mathematics Applied to Business and six graduate programs leading to M.S. and Ph.D. degrees. Moreover, when analyzing the different courses of FFCLRP, they represent typical academic organization in Brazil and Latin America and could be taken as a model for analyzing other Brazilian research institutions. This analysis was made using: 1) the total number of papers (indexed in Curriculum Lattes database), 2) the number of papers indexed by Thomson ISI Web of Science database, and 3) the Hirsch (h-index). Bibliometric evaluations of undergraduate courses showed a better performance of the courses of Chemistry (P < 0.05), Biology (P < 0.05) and Medical Physics (P < 0.05) when compared to the Pedagogy, Sciences of Information and Documentation (P < 0.05) and Psychology (P < 0.05). We also analyzed the scientific output of the six graduate programs of FFCLRP-USP: 1) Chemistry, 2) Physics Applied to Medicine and Biology, 3) Entomology, 4) Compared Biology, 5) Psychology, 6) Psychobiology. The graduate programs in Psychobiology, Chemistry, Physics Applied to Medicine and Biology, Compared Biology, and Entomology presented very similar results, concerning the assessment of the three indexes. The graduate program in Psychology presented a lower h-index (P < 0.05) and had fewer papers indexed by the ISI (P < 0.05) when compared to the other graduate programs. The worse performance of the psychology program, pedagogy, sciences of information and documentation, psychology courses may be associated to the limited coverage of ISI database and some particular characteristics of this field of concentration.
Scientific bibliographic productivity at FFCLRP-USP (undergraduate courses and graduate programs): An application of the h-index
Keywords: Bibliometric indicators; Information science; Scientific publication indicators; conference paper; data base; health physics; health program; information science; medical education; medical research